A Two-in-One Tumor in the Adrenal: A Functional Adrenocortical Adenoma with Myelolipomatous Differentiation. (2nd January 2023) - Bhardwaj, Sunny; Deshpande, Rohit Sanjay; Kumar, Santosh; Mitra, Suvradeep
Abstract: Background: Adrenocortical adenoma (ADA) and myelolipoma are two common benign neoplasms of the adrenal cortex that have been reported to occur together. Case report: A 14-year-old girl presented with the features of ACTH-independent endogenous Cushing syndrome. Abdominal CECT revealed a left adrenal 2.3 × 1.8 × 1.5 cm arterially enhancing nodular lesion with central hypodensity. Histologically, this was an ADA with oncocytic change and myelolipomatous differentiation/metaplasia. Discussion/Conclusion: ADA with myelolipomatous differentiation/metaplasia can occur in the pediatric age group.